Increased light‐use efficiency in northern terrestrial ecosystems indicated by CO2 and greening observations. Issue 21 (4th November 2016) - Thomas, Rebecca T.; Prentice, Iain Colin; Graven, Heather; Ciais, Philippe; Fisher, Joshua B.; Hayes, Daniel J.; Huang, Maoyi; Huntzinger, Deborah N.; Ito, Akihiko; Jain, Atul; Mao, Jiafu; Michalak, Anna M.; et al.
Abstract: Observations show an increasing amplitude in the seasonal cycle of CO2 (ASC) north of 45°N of 56 ± 9.8% over the last 50 years and an increase in vegetation greenness of 7.5–15% in high northern latitudes since the 1980s. However, the causes of these changes remain uncertain. Historical simulations from terrestrial biosphere models in the Multiscale Synthesis and Terrestrial Model Intercomparison Project are compared to the ASC and greenness observations, using the TM3 atmospheric transport model to translate surface fluxes into CO2 concentrations. We find that the modeled change in ASC is too small but the mean greening trend is generally captured. Modeled increases in greenness are primarily driven by warming, whereas ASC changes are primarily driven by increasing CO2 . We suggest that increases in ecosystem‐scale light use efficiency (LUE) have contributed to the observed ASC increase but are underestimated by current models. We highlight potential mechanisms that could increase modeled LUE. Key Points: Current terrestrial biosphere models underestimate northern CO2 seasonal cycle amplitude increase Models capture observed greening trends and therefore increased uptake of light by ecosystems Reconciling these suggests an increase in ecosystem light use efficiency larger than models simulate